Tailoring the Reaction Pathway for Control of Size and Composition of Silver-Gold Alloy Nanoparticles - Traore, Nabi; Berthold, Michelle; Hartmann, Lukas; Schmul, Patricia; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Journal of Physical Chemistry C, 2024)
In this work, we independently tune both the particle size and the chemical composition of bimetallic silver−gold alloy nanoparticles (NPs) by carefully controlling the reaction pathway. NP synthesis involves control of the supersaturation profile in time and space. For the reaction-controlled case, this supersaturation profile is determined by a network of reactions leading to the buildup of the monomer concentration. Using a variety of characterization tools, we show how the process conditions influence the coupled reactions in the complex formation mechanism of Ag−Au alloy NPs. Applying a simple mass balance allows for the independent control of size and chemical composition of these NPs, yielding particles with constant composition and varying size in the range of 20 to 40 nm. A series of constant sizes and varying chemical compositions in the range of 10% to 100% molar gold content is also possible. Our new methodology shows an example of how reaction networks can be tailored to achieve targeted NP properties and paves the way for better control in the synthesis of multicomponent NPs.<br